Using Stable Carbon and Nitrogen Isotopes to Investigate the Impact of Desalination Brine Discharge on Marine Food Webs - Grossowicz, Michal; Sisma-Ventura, Guy; Gal, Gideon (Frontiers in Marine Science, 2019)
Stable isotope ratios were used to trace the impact of anthropogenically derived brine from desalination plants on organisms at different trophic levels (primary producers and consumers) along the highly urbanized ultra-oligotrophic Israeli coast (southeast Mediterranean). Primary producer and consumer organisms were collected from two sampling stations at two desalination plants sites: an “Impacted station”, near the brine discharge outlets, and a “Control station” situated further offshore to the impacted zone. δ(_^13)C and δ(_^15)N values of both producers and consumers displayed minor variations between the impacted and control stations, indicating little effect of brine discharge on the coastal trophic structure. The coastal δ(_^15)N values were generally higher than those of similar pelagic communities of the southeastern Mediterranean. These were particularly high in benthic invertebrates and benthic carnivores (fish) from the southern site, where high anthropogenically N loads from ground water amelioration are discarded alongside the brine. The observed differences in the δ(_^15)N of the benthic components between the two study sites suggest that brine derived density plumes from desalination plants are a possible vector of nutrients to benthic communities. The results indicate that the benthic components were the most sensitive group to anthropogenic derived N pollution, and provide insight into site-specific processes.